Welfare effect of international migration on the left-behind in Ghana: Evidence from machine learning. (15th September 2020) - Martey, Edward; Armah, Ralph
Abstract: This article examines the effect of international migration on household expenditure, labor outcomes, and poverty on the left-behind household members in Ghana using nationally representative data. The study contributes to the literature in terms of the methodology employed to reinforce the welfare effect of international migration in a developing country like Ghana. The results suggest that international migration increases household expenditures, which is largely driven by investments relative to expenditure on consumption goods. In addition, transfer of remittances to left-behind household members by migrants results in a reduction of their weekly working hours in the labor market and modestly reduces household poverty. The findings of the study suggest that the gains from international migration can be consolidated with favorable policy environment that ensures flexible conditions and terms of borrowing from banks to finance the initial expenditure related to migration. In addition, reduction in remittance transfer charges is likely to increase transfer through the formal systems, which can be captured and used for future planning.